2013
DOI: 10.18097/pbmc20135905530
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases (MMP) - MMP-1,-2,-9 and its endogenous activity regulators in transformed by E7 oncogene HPV16 and HPV18 cervical carcinoma cell lines

Abstract: Учреждение Российской акадамии медицинских наук Научно-исследовательский институт биомедицинской химии имени В.Н. Ореховича РАМН, 119121, Москва, ул. Погодинская, 10; факс: (495)245-0857; эл. почта: Nina.Solovyeva@ibmc.msk.ruМатриксные металлопротеиназы (ММП) играют ключевую роль в развитии инвазии и метастазирования опухолей. Цель настоящей работы -выяснение особенностей экспрессии ММП-1, ММП-2, ММП-9, и регуляторов их активности: активатора плазминогена -уАП и тканевых ингибиторов ММП -ТИМП-1, ТИМП-2 в кле… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…HeLa cell lines are transformed by Human papillomavirus 18 [ 24 ], and Human papillomavirus types 16 and 18 are the most common strains in Taiwan, accounting for nearly 70% of all cervical cancer cases [ 1 ]. Acute myeloid leukemia (AML) is the most common form of leukemia in adults; therefore, human AML cell line U937 was used as the raw material in our study.…”
Section: Resultsmentioning
confidence: 99%
“…HeLa cell lines are transformed by Human papillomavirus 18 [ 24 ], and Human papillomavirus types 16 and 18 are the most common strains in Taiwan, accounting for nearly 70% of all cervical cancer cases [ 1 ]. Acute myeloid leukemia (AML) is the most common form of leukemia in adults; therefore, human AML cell line U937 was used as the raw material in our study.…”
Section: Resultsmentioning
confidence: 99%
“…The dissolution of the basement membrane caused by MMP in tumors is a notable process in the movement of tumor cells. A significant correlation has been reported between the activation of MMP and the migration and invasion of tumor cells ( 32 , 33 ). The expression of MMP2 and MMP9 was observed to be higher in patients with lymph node metastases compared with patients without lymph node involvement in oropharyngeal SCC ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we found that the transformation of broblasts with the E7 HPV16 oncogene was accompanied by the induction of MMP-1 expression [42,45]. The study of MMP expression, carried out by us on E7 HPV16-associated samples of PCSM tumors, showed that the main contribution to the invasive and metastatic potential of the tumor is made by an increase in the expression of collagenases and, rst of all, MMP-1 along with MMP-9, which can serve as markers of invasive and metastatic potential tumors [44][45][46]. In previous our studies, the expression of MMP-1 and EMN in SCC was found both in the cervical tumor and in the stroma of the tumor and uterine tissue, and the expression of MMP-1 in normal tissue was at a lower level than in the tumor, and the level of EMN expression did not change signi cantly.…”
Section: Discussionmentioning
confidence: 99%